Study guide to accompany Engineering mechanics. Volume 2 : Dynamics. - Meriam, J. L. (James L.); Henderson, J. M. (New York ; Chichester : John Wiley and Sons, 1997)
Definitions and principles. Units. Problem formulation. Analysis techniques. Rectilinear motion. Equations of motion. Work-energy. Impulse-momentum...
Keywords: Engineering; Mechanics; Dynamics; Applied; Mechanics, Applied -- Problems, exercises, etc; Dynamics -- Problems, exercises, etc